(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
The paper presents a comparative analysis of physical preparedness level indices of forwards of rugby national team Ukraine U-18 and Kharkiv oblast team. The growing competition in home sports tournaments sets forth significant demands to the level of physical preparedness of players individually and teams overall. At present-day stage of the development of sports games, the issue of differences in preparedness of athletes according to their playing position becomes urgent. Thus, high level of physical preparedness of forwards in rugby is a significant index of their competition activity efficiency. Analysis of these aspects will contribute to increasing the level of physical fitness of individual players and the team as a whole. Therefore, the aim of the article is to compare strength indices of physical preparedness of forwards of various sports qualification in rugby. To achieve the aim, a pedagogical survey of the level of development of strength capacity of forwards from rugby national team Ukraine and Kharkiv oblast team was done. The results of five tests that are most often used to assess the level of physical preparedness of athletes in varieties of rugby were used as the data to identify strength preparedness of qualified forwards from both teams. Comparative analysis of the level of physical preparedness of forwards has proven prevalence of athletes from Slobozhanshchyna region over athletes from national team Ukraine U-18 by all indices. In general, the obtained data adequately reflect the level of strength preparedness of forwards from the aforementioned teams and, therefore, prove that the applied strength tests directly of indirectly reflect the level of preparedness of forwards from both teams to competition activity.